Interculturality and Educational Research in Higher Education - Mancila-Mancila, Iulia (My University, 2019)
The demands and challenges of university contexts are leading to a change in the educational model towards a different one, which requires an increasing development of educational policies and practices that advocate for an inclusive intercultural education where all students could participate and learn together regardless their differences. Specifically, in this paper, I briefly report on my personal and professional experience as a university teacher and researcher, participating in various research projects exploring how I understand diversity and intercultural education in our daily practice as university teachers, what barriers and difficulties are the most common and what suggestion of transformations could be generated through this process.
Keywords: Investigación educativa; Educación superior; Interculturality; Research; HE